2018
DOI: 10.1002/2017tc004815
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Paleomagnetic Rotations in Sicily: Thrust Versus Strike‐Slip Tectonics

Abstract: The paleomagnetic investigation of the western Sicily Maghrebian belt has revealed since the 1970s that large clockwise rotations up to 140° with respect to the Hyblean‐African foreland occurred synchronous with Tertiary shortening of the chain. The observation that rotations decrease stepwise from internal to external tectono‐stratigraphic units led in the 1990s to a widely accepted model postulating that rotational thrust‐sheet emplaced during forward orogenic propagation. More recently, other authors sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 67 publications
2
34
0
Order By: Relevance
“…Crustal rotations that have taken place in deformed orogens have been either related to block rotation due to strike‐slip shear (Hernandez‐Moreno et al, , and references therein) or to emplacement of rotational thrust sheets (e.g., Cifelli & Mattei, ; Shaanan et al, ; Speranza et al, ; Weil et al, ). Both kinematics are possible in the study area, as the Lanping and Simao domains are characterized by both strike‐slip faults, and thrust structures (Bureau of Geology and Mineral Resources of Yunnan Province, ; Wang & Burchfiel, ).…”
Section: Discussion: Crust Fragmentation Within the Simao And Lanpingmentioning
confidence: 99%
“…Crustal rotations that have taken place in deformed orogens have been either related to block rotation due to strike‐slip shear (Hernandez‐Moreno et al, , and references therein) or to emplacement of rotational thrust sheets (e.g., Cifelli & Mattei, ; Shaanan et al, ; Speranza et al, ; Weil et al, ). Both kinematics are possible in the study area, as the Lanping and Simao domains are characterized by both strike‐slip faults, and thrust structures (Bureau of Geology and Mineral Resources of Yunnan Province, ; Wang & Burchfiel, ).…”
Section: Discussion: Crust Fragmentation Within the Simao And Lanpingmentioning
confidence: 99%
“…As previously noticed, moderate differential rotation between coeval tectonostratigraphic units within the wedge, and major decreasing rotation through time, evidenced by paleomagnetic data (Cifelli et al, 2007;Speranza et al, 2018), are not consistent with large displacements between long thrust sheets (Butler et al, 2019).…”
Section: Ii22 Tectonic Style and Accommodation Of Crustal Shorteningmentioning
confidence: 58%
“…This period was also characterized by large vertical-axis clockwise rotations of the thrust system in response to the convergence obliquity. Up to 70° regional rotations of Upper Triassic-Middle Miocene successions are recorded by paleomagnetic measurements (Channell et al, 1990;Oldow et al, 1990;Speranza et al, 2003Speranza et al, , 2018 and structural analysis (Monaco and De Guidi, 2006;Avellone et al, 2010;Barreca and Monaco, 2013).…”
Section: Ii15 -Middle To Upper Miocene (Serravalian To Messinian)mentioning
confidence: 99%
“…The remaining question is whether a similar evolution may occur along the North African margin toward the West and East of the Mitidja‐Cheliff‐Northwestern Algeria areas, that is, in Morocco and Eastern Algeria‐Tunisia. Further East, paleomagnetic investigation of the western Sicily Maghrebian belt has revealed that large clockwise rotations with respect to the Hyblean‐African foreland have occurred since the Tertiary (Channell et al, ; Schult, ; Speranza et al, ).…”
Section: Resultsmentioning
confidence: 99%